CROSSFIT TRAININGS AS AN ALTERNATIVE APPROACH TO PREVENT THE PERFORMANCE LOSS DURING THE REST OF THE END OF SEASON IN ELITE WRESTLERS - Ozbay, S.; Akbulut, T.; Cinar, V. (South Ural State Univ, Scientific Research Dept, 2019)
Aim. The objective of this study is to investigate the effectiveness of Crossfit training in order to minimize performance loss of elite wrestlers during 30-day rest period. Materials and Methods. Total 23 elite male wrestlers who competed at the last national championship participated in this study. The participants were divided into two groups as Crossfit and control group. The Crossfit group performed 5 pull-ups, 10 push-ups and 15 squat exercises consecutively (Crossfit-Cindy) for total 20-min, during the 30-day period, 6 days per week. The Control group did not perform any exercise programs during this period. Before and after the 30-day period, athletes were applied anthropometric measurements as well as VO(2)max (aerobic capacity), bench press and squat (maximal dynamic strength), leg and handgrip strength (isometric strength), pull-up and push-up (strength endurance) tests. Results. After the 30-day period in the control group, body weight and body fat percentage (BF %) increased significantly, whereas all performance variables decreased significantly. Maximal dynamic strength and aerobic capacity values decreased significantly in the Crossfit group, while body weight, body fat percentage, isometric strength and strength endurance values were maintained. Moreover, the decrease in VO2max and bench press tests was higher in the control group than in the Crossfit group. Conclusion: Consequently, the present study showed that 20-min Crossfit training was highly effective in maintaining the form of elite wrestlers during a 30-day rest period.
Keywords: Wrestling; CrossFit; Strength; isometric force